Thymic carcinoma - Machado, Vitória Homem; Pivatto Júnior, Fernando; Torres, Felipe Soares (Clinical and Biomedical Research, 2016)
Thymic carcinomas are a heterogeneous group of aggressive, invasive epithelial malignancies. Their incidence is rare, occurring predominantly in middle-aged men. Here we present the typical imaging findings of a thymic carcinoma. The combination of imaging characteristics with tumor location and patient age provides a roadmap for approaching the differential diagnosis. Keywords: Thymus Gland; carcinoma; mediastinal neoplasms